Connotative And Denotative In E-News : Discourse Study Of Covid-19 Outbreak - Junita, Rizka (Universitas Muhammadiyah Sumatera Utara, 2021)
Semantics as the study of meaning stands at the very center of the linguistic quest to understand the nature of language and human language abilities. It is obvious that semantics has an important role in understanding and comprehending a language, especially for english. The aim of study is to elaborate the semantic both connotative and denotative are used in the E-News about covid-19 outbreak, to classified which the theme and rheme of textual function of discourse analysis in E-News about covid-19 outbreak. This study used descriptive qualitative method in analyzing the data. The data was taken from E-News namely Jakarta Post. The script consisted of 3 pages were taken as the data. The data were 29 sentences. The realization parts of textual function occured because the clauses have grammatical and systematical reason. Its hope that the result of this study will be useful to everyone who wants to study meaning.